A study on factor influencing employee motivation in work environment - MS. B. NEERAJA,; MR. P. NIRANJAN, (The journal of contemporary issues in business and government, 2020)
Representatives are the main resources of an association. Additionally, in the present exceptionally serious world representatives are the elements which decide achievement or disappointment of an association. They are the ones who cooperate with the client on an everyday premise and complete the entire activity. As such the associations need to focus on the happiness of the representatives. What's more, as quality HR gets an ever increasing number of meager, the organizations need to pay more notice as per the general inclination of workers. Likewise, notwithstanding the fulfillment of the representative, the business has a task to carry out in the inspiration of the worker. In the event that the worker is propelled towards the work, at that point it is probably going to yield more outcomes.